Efeitos individuais e interativos da diversidade de detritos, contexto e variabilidade ambiental sobre a magnitude e estabilidade do processo de decomposição - Morais, Ana Clézia Simplício de (2012)
Studies on the effects of changes in biodiversity and ecosystem functioning have been a central theme in ecology over the past two decades. Several studies have showed that the diversity of plant debris differently affects the decomposition process in aquatic and terrestrial environments, but we know very about the effects of detritus diversity on decomposition under fluctuating environmental conditions. We tested whether and how the environmental contexts, as well as the dynamic of their alternation, influence the effects of detritus diversity on the decomposition process. We performed a field experiment where we manipulate the litter diversity of 8 species of terrestrial plants decomposing (litterbags) in single and in mixture containing the eight species together in three different environmental contexts: the terrestrial environment (T), aquatic (A) and interface (I) - experimental treatment that simulates variation in flooding regime. We measured the rate of decomposition through the loss of mass of the community and each individual detritus in monocultures and mixtures. Species richness and environmental variability had no effects on the magnitude and stability of the decomposition process. However, there were significant diversity effects on the decomposition of an individual alien species, F. benjamina. Environmental context had significant effects on the magnitude and variability of decomposition. Detritus decomposition was faster and more variable on aquatic, interface and terrestrial conditions, respectively. Our results demonstrate that the diversity of plant detritus has minor effects to the decomposition across disparate environmental conditions and suggest that it is necessary to consider the potential of other abiotic factors in affect the magnitude and variability of the decomposition processes